Distribuição espaço-temporal de diagnóstico de raiva bovina na área da abrangência da Delegacia Regional do Instituto Mineiro de Agropecuária em Belo Horizonte - 1998-2004. - Alexandre Jose Teixeira Fernandes (2007)
The purpose of this study is to describe the space-time evolution of the diagnosis of bovine rabies in the Belo Horizonte regional department of the Instituto Mineiro de Agropecuária (Agriculture and Livestock Institute) from 1998 to 2004, and correlate it to spacial variables, through current Spacial Epidemiology methodologies and other tools such as Geoprocessing and SIGs. Through a directed bibliographic search it goes over the concepts of modern Epidemiology, the characteristics of bovine rabies and the factors related to it, be them biologic, socio-political or economic. This study will start with a descriptive study of the bovine rabies phenomenom and develops into a spacial exploratory analysis of three disease clusters, SaTScan® results, with the purpose of recognizing the phenomenoms behaviour in relation to the following variables: bovine livestock density by district, altitude, drainage, roads, train ways, and soil cover. The studied region has favorable environmental conditions (both natural and artificial) for the diseases main vector (Desmodus rotundus). The disease showed greater risk in rural areas bordering natural areas, at altitudes varying from 500 to 1500 meters, in the inluence area of the rivers present in the studied region. There are determining factors for bovine rabies in the studied region, such as ecological factors, socio-political factors and economical factors. Bouts of bovine rabies in the region occur as a result of environmental changes, such as has been occuring in the region of the Moeda Mountain Range and the Itacolomi Park (Ouro Preto and Mariana).